CORPORATE GOVERNANCE, OPINI GOING CONCERN, SUBSEQUENT EVENT DAN AUDIT REPORT LAG - Sigit Handoyo; Nur Hasanah (Jurnal Aplikasi Bisnis, 2018)
Audit Report Lag is completion time of the annual financial audit statements from the date of company book closing up to the date of the audit report. This research represents empirical study to know influence of corporate governance, going concern opinion, and subsequent event toward Audit Report Lag.The populations of this research are all of manufacturing companies listed on Indonesia Stock Exchange in 2013. Samples of this research are 137 companies and the method of data analysis is using descriptive and doubled regression analysis. To obtain model of regression which representative is hence conducted by test of classic assumption. The result of descriptive statistic indicate that mean of an audit report lag in 2013 is 76,0146 days. The result of this research shows that the size of the board of directors, audit opinion and going concern opinion significant effect on Audit Report Lag. Furthermore, Independence board of directors, audit committee independence and subsequent event have not influence toward Audit Report Lag.